Balanced Scorecard sebagai Strategi Inovatif Peningkatan Mutu Pendidikan Berkelanjutan di Era Transformasi Digital: The Balanced Scorecard as an Innovative Strategy for Continuous Quality Improvement in Education in the Era of Digital Transformation - Sudiansyah, Sudiansyah; Peterianus, Septian (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to understand the implementation of the Balanced Scorecard (BSC) as an innovative strategy for enhancing the quality of sustainable education in the digital transformation era. The background of this study is predicated on the need for educational institutions to manage quality in a more structured, reflective, and adaptive manner in response to change. This study employs an exploratory qualitative approach with a multiple case study design. Data were collected through in-depth interviews, observation, and documentation studies at two high schools with different institutional characteristics. The findings indicate that the BSC can serve as an effective strategic management tool, incorporating five complementary perspectives: stakeholders, internal processes, learning and growth, financial, and strategic sustainability. The application of the BSC was shown to improve governance efficiency, strengthen a reflective culture, and align school strategies with national policies such as Merdeka Belajar (Freedom to Learn) and the objectives of SDG 4. The conclusion of this research affirms that the BSC is not merely a technical measurement tool, but also a reflective framework capable of fostering a more adaptive, participatory, and sustainable education system.